The role of omalizumab in the treatment of severe allergic asthma - Chapman, Kenneth R (Pulsus Group Inc, 2006)
BACKGROUND: A novel anti-immunoglobulin E (anti-IgE) therapy for asthma, omalizumab, has been approved for use in Canada. OBJECTIVE: To review the basic and clinical data for omalizumab, and to examine its possible role for asthma management in Canada. METHODS: A literature search from 1960 to 2006 was conducted in MEDLINE to identify studies of omalizumab. In addition, abstracts from recent respiratory and allergy scientific meetings were sought, and any unpublished data were requested from the manufacturer. A consensus panel of respiratory and allergy specialists reviewed and summarized the data, and derived a set of recommendations for omalizumab use. RESULTS: Omalizumab is a humanized monoclonal antibody designed to bind to the C epsilon 3 domain of the IgE molecule, forming soluble immune complexes that are cleared by the reticuloendothelial system. Subcutaneous injections, given at two- or fourweek intervals at the recommended dose, result in a rapid decrease in free circulating IgE levels. In two phase III clinical trials of 1405 adult and adolescent patients with moderate to severe asthma maintained on moderate doses of inhaled corticosteroids (ICS), omalizumab reduced exacerbation rates compared with placebo, and was associated with improved symptoms and a greater corticosteroid-sparing effect. In a trial of 419 patients with severe disease that was uncontrolled despite the use of high-dose ICS and concurrent long-acting beta(2)-agonists, severe exacerbations were 50% less frequent in omalizumab-treated patients than in control subjects. Retrospective analyses have identified the characteristics of patients most likely to respond to omalizumab treatment. RECOMMENDATIONS: Omalizumab may be considered as a potential adjunctive therapy in atopic patients with severe asthma uncontrolled by conventional therapy with optimal doses of ICS and appropriate adjunctive therapy (eg, long-acting beta(2)-agonists). Typically, patients are identified by the need for frequent short course or continuous oral corticosteroids. Therapy should be initiated only after review by a specialist to confirm the diagnosis and that conventional therapy is optimal.